"Out-of-Pocket Expenditure", Abolition User Fees and the Quality of Health Services Provided by Public Health Centers IVs in Uganda: A Case of Health Centre IVs in Rujumbura Health Sub District; Rukungiri - Kijjambu F., Dr. Nsambu; Kule John, Dr. Baguma; Katarangi K., Asaph; N., Tumwebembaire (European Journal of Health Sciences, 2023)
Purpose: The study intended to investigate inadequate health financing as challenge in Uganda, the study population included residents of Rujumbura Health sub district in Rukungiri who have lived in the place for a period exceeding fifteen years, being served by Bugangari and Buhunga Health center IVs. The study was guided by the following specific objectives; to establish whether there is no longer "out of pocket expenditure" in public health centers IVs in Uganda; To establish the effect of "out-of-pocket expenditure" on the quality of health services provided by public health centers IVs in Uganda.to establish the effects of abolishing user fees on the quality of health services provided by public health centers IVs in Uganda. Methodology: It was a cross-sectional study, which was inclined to quantitative approaches Findings: The study findings indicated that there is a positive relationship with out of pocket expenditure and the quality of health services provided however, results in the model summary concludes that "˜out of pocket expenditure explain 38.9% of the changes in quality of health services and the remaining 61.1% may be explained by other factors consistent with the overall effect of abolishing "out of pocket" expenditure in the study area. Recommendations: The policy implication emerged from this study indicates that the quality of health services will be at optimum if users' fees are in order to foster further improvement rather than abolishing user fees in health center IVs at a reasonable amount which is affordable by citizen. Especially aby adopting private and user free wings. More Qualified medical officers should be deployed at these levels to increase on the image of health center IVs, purposely to increase the confidence and trust by patients to medical officers when they are being treated. A policy on out of pocket expenditure is crucial in improving on cost efficiency and to protect "patients "New technology" in the hospital should be adopted in these health center IVs to improve on the corporate images of these health facilities and also to provide appropriate diagnosis and prescription. Information on hospital rules, regulations and procedures should be provided and can easily be accessible at the hospital and even before. Further studies should be carried out to establish the optimum adequate out of packet expenditure to be charged to the patients at respective health facilities in the country for particular illness and consultation